Synthesis, Crystal Structures and Properties of Ferrocenyl Bis-Amide Derivatives Yielded via the Ugi Four-Component Reaction - Zhao, Mei (Molecules, 2017)
Ten ferrocenyl bis-amide derivatives were successfully synthesized via the Ugi four-component reaction by treating ferrocenecarboxylic acid with diverse aldehydes, amines, and isocyanides in methanol solution. Their chemical structures were fully characterized by IR, NMR, HR-MS, and X-ray diffraction analyses. They feature unique molecular morphologies and create a 14-membered ring motif in the centro-symmetric dimers generated in the solid state. Moreover, the electrochemical behavior of these ferrocenyl bis-amides was assessed by cyclic voltammetry.